White Plaque in Diabetes Mellitus Patients (Case Report of UNSOED RSGM Patients) - Dhartono, Agung Prabowo; Cahyani, Inneke (Jurnal Medali, 2024)
Introduction: Coated tongue is a condition where the surface of the tongue looks white or other colors which is a pile of debris, food debris and microorganisms found on the dorsal surface of the tongue. The pile occurs due to systemic factors that affect the condition of the oral cavity, one of which is diabetes mellitus. Diabetes mellitus is a metabolic disorder caused by a lack of insulin secretion or decreased tissue sensitivity to insulin and is characterized by hyperglycemia. Case Report: A 44-year-old woman came to RSGM UNSOED complaining of white patches on the tongue since the last few years. There is a lesion in the form of a yellowish white plaque, can be scraped some parts leaving a red color, some parts leaving a white color that cannot be scraped, plaque measuring more than 1 cm, does not hurt when scraped, and is irregular in shape. The corners of the patient's mouth appear dry. The patient suffers from systemic diabetes mellitus and is taking medication. Discussion: High glucose levels in patients with diabetes mellitus affect the salivary content. This increase in glucose levels results in the content of biofilm layers and plaque on the surface of the teeth and tongue which serves as a place for bacterial attachment. Bacteria will multiply more well because of sufficient food intake. White spots occur due to the accumulation of microorganisms and debris due to the content and lack of salivary glands, causing the quality and quantity of saliva production in the oral cavity to decrease, so that people with diabetes mellitus tend to have poor OH and bad breath odor if dental cleaning is not done regularly. Conclusion: White plaque on the tongue occurs due to the accumulation of microorganisms and debris due to the lack and change in salivary gland content due to high sugar levels in patients with diabetes mellitus